Differences In Perceptions Of Women And Men In Waste Management In Tenggilis Mejoyo District, Surabaya City - Susi A. Wilujeng; Andriyanto Andriyanto (Eduvest - Journal of Universal Studies, 2024)
In this study, community perceptions of waste management will be analyzed by comparing perceptions between female and male communities. The research was conducted in this sub-district with stratified random sampling, with descriptive statistical analysis to provide an overview of the variables that have been measured, then displayed in the form of graphs and diagrams. This study also tested hypotheses for 11 problem formulations with six variables, namely three independent construct variables (X), two intervening variables, and one dependent construct variable (Y). The results showed that most of the women did not know what household-specific waste was and did not sort their waste because they did not have time. The type of waste that is mostly segregated is small electronic waste and female respondents tend to sell segregated specific waste to collectors. As for men, most of them do not know what household-specific waste is and do not segregate waste because they do not have time. The most segregated type of waste is small electronic waste and male respondents tend to keep the segregated specific waste. Based on the results of hypothesis testing, it can be concluded that in women, most variables affect each other or have a positive influence. Knowledge and norms do not affect intention, while attitude and perception do not affect behavior. In men, only a small number of variables influence each other or have a positive influence. Attitude influences intention, norms influence behavior and perception, and intention influences behavior.